Debatable Issues in Fiqh Al-Zakat: A Jurisprudential Appraisal - Mahmud, Mek Wok; Shah Haneef, Sayed Sikandar (Jurnal Fiqh, 2008)
Zakat in terms of socio-economic role is a mandatory religious duty on the well to do members of the Ummah, to part with a portion of their wealth for the well-being of have-nots and helping other eligible social causes. To practically implement this policy, the Prophet laid down a comprehensive legal framework for its collection and distribution befitting the condition of his time. The classical jurists supplemented it by framing other operational laws to realize efficacious implementation of zakat at their time. In our contemporary time, jurists were faced with the question of efficacy of classical elaboration of zakat jurisprudence to serve the socio-economic objectives of zakat in modern time. Among others the adequacy of classical definition of zakat terms became debatable. The result was the usual divergence of opinions among the contemporary thinkers both with Shari?ah and Islamic economics backgrounds. This study is primary designed to critically evaluate the opposing views from fiqh perspective.